EFEKTIFITAS FILTER KARBON AKTIF DALAM MENURUNKAN KADAR MANGAN (Mn) DAN BESI (Fe) DALAM AIR TANAH PUSKESMAS KELAPA DUA KABUPATEN TANGERANG - Charles Situmorang (FT-USNI, 2018)
Humans and other living things are very dependent on water to sustain their lives. Based on the results of external supervision conducted by the Tangerang District Health Office in 2016, the quality of clean water in the Kelapa Dua Health Center contained Mn and Fe with levels exceeding the quality standard. Based on Minister of Health Regulation 416 of 1990, Manganese (Mn) levels in allowed drinking water are 0.5 mg / lt, Iron (Fe) 1.0 mg / lt, In this Data Analysis Technique including data processing techniques carried out by linear regression of data set as research variables. Based on the results, the following conclusions are obtained, the efficiency of activated carbon media with a media thickness of 90 cm in reducing Fe content in water by 39.38%, the efficiency of activated carbon media with a media thickness of 90 cm in reducing Mn content in water by 81.82%. There is a significant effect of filtration treatment on Fe, and Mn content. The thicker the filtration media, the better degradation of Fe, and Mn.